Biodiversity and sustainable use of coastal waters 21th-25th August 1995 Tjarno Marine Biological Laboratory, Sweden. - Hedlund, L.; Hagerhall, Bertil; Johannesson, Kerstin (Swedish Scientific Committee on Biological Diversity, 1995)
Discussion paper no.2